Orthodontic Bracket Adjustable In Different Angles - Ibrahim Alshahrani; Ali Alhaizaey (KARACHI MEDICAL AND DENTAL COLLEGE, 2024)
Modern advancements in dentistry, like as laser technology and digital dentistry, are increasing the comfort and effectiveness of dental procedures. Dental lasers, for instance, can now be utilized more precisely and less invasively for treatments like gum contouring and cavity elimination. The orthodon- tic brackets with adjustable angles, presenting a paradigm shift in orthodontic treatment. These brackets offer unprecedented versatility, enabling orthodontists to customize treatment for diverse cases with unique tooth anatomy and complex malocclusions. The adjustable feature enhances pre- cision and efficiency in tooth movement, potentially reducing treatment time. While promoting im- proved patient comfort through a tailored approach, the technology demands specialized training for effective utilization. The advantages include enhanced versatility, precision, and potential for more efficient outcomes. However, considerations of complexity, maintenance, and associated costs under- score the need for careful assessment and training in incorporating these innovative brackets into orthodontic practice. Overall, adjustable angle brackets signify a promising advancement, balancing customization with practical considerations for optimal orthodontic care